2014
DOI: 10.1371/journal.pone.0098241
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Hybrid Model with Seasonal Auto-Regressive Integrated Moving Average (ARIMA) and Nonlinear Auto-Regressive Neural Network (NARNN) in Forecasting Incidence Cases of HFMD in Shenzhen, China

Abstract: BackgroundOutbreaks of hand-foot-mouth disease (HFMD) have been reported for many times in Asia during the last decades. This emerging disease has drawn worldwide attention and vigilance. Nowadays, the prevention and control of HFMD has become an imperative issue in China. Early detection and response will be helpful before it happening, using modern information technology during the epidemic.MethodIn this paper, a hybrid model combining seasonal auto-regressive integrated moving average (ARIMA) model and nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 33 publications
3
60
0
Order By: Relevance
“…ARIMA attempts to predict the future values based on auto-regressive and moving average techniques [63,64]. Unlike ARIMA, that focuses only on a few number of past instances observed just before, S-ARIMA exploits a larger number of past instances to consider the seasonal patterns throughout them [65]. The parameters for the two models were set to be the same as presented in [64,66].…”
Section: Input Valuesmentioning
confidence: 99%
“…ARIMA attempts to predict the future values based on auto-regressive and moving average techniques [63,64]. Unlike ARIMA, that focuses only on a few number of past instances observed just before, S-ARIMA exploits a larger number of past instances to consider the seasonal patterns throughout them [65]. The parameters for the two models were set to be the same as presented in [64,66].…”
Section: Input Valuesmentioning
confidence: 99%
“…In the original training dataset, we used four of the twelve original samples to train the network, so that the N 2 (non-linear part of Z 2 dataset, which is the training set) group could be fitted. Finally, the estimated values from the neural network N are then added to the estimated ARIMA values, so we have the final estimation model for Z, which is given by equation (6).…”
Section: Neural Network Fitting: Original Samplesmentioning
confidence: 99%
“…Some other studies related to what we propose in this work can be seen in [3][4][5][6][7][8][9][10][11]. In the study by Liangping and Sternberg, two approaches are proposed to predict the Peak Signal-to-Noise Ratio (PSNR) in video transmissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…average (ARIMA) model [1,6,[8][9][10][11]. Pan et al found the ARIMA model preferable to the GM (1,1) gray system model in predicting HFMD by comparing their outputs [6].…”
mentioning
confidence: 99%